Methodology of integrated knowledge in Islamic economics and finance: collective ijtihad - Ildus, Rafikov; Akhmetova, Elmira (Emerald, 2020)
Purpose – The purpose of this paper is to discuss the methodology of integrated knowledge in Islamic economics and finance and seek to offer collective ijtihad as one way to find solutions to the existing problems in the field. Design/methodology/approach – The study is based on the idea of multidisciplinarity or interdisciplinarity, which uses not only traditional sources of Islam and economics, such as u sūl al-fiqh, fiqh mu’amalat, econometrics, statistics, microeconomics and macroeconomics but also looks into behavioural and natural sciences for inspiration and solutions. This paper is constructed using the methodology of “the two readings”, as promoted by the International Institute of Islamic Thought, and which combines the revealed and the existential sciences. Findings – This paper proposes the collaborative multidisciplinary methodology as the main approach to studying the modern problems and challenges, as well as for finding solutions in the fields of Islamic economics and finance. Practical implications – Studying and researching issues, particularly in the field of Islamic economics and finance, from an interdisciplinary perspective, effectively broadens practical applications and possibilities in Islamic finance. Originality/value – This paper contributes to social sciences, especially the field of Islamic finance, and calls upon researchers to engage in multidisciplinary studies.